Intermediates Trade and Knowledge Flows - Michael Koch; Antonella Nocco (CESifo GmbH, 2025)
This paper introduces a novel mechanism by emphasizing benefits for firms through participation in buyer networks among firms that source the same locally produced inputs. In a first step, we utilize register-based data from Denmark to generate a firm-specific buyer network variable which relies on firms' industrial input structures and imports. Utilizing this proxy we provide evidence of cost savings from network participation, as larger buyer networks reduce firms' input demand. Subsequently, we develop a trade model incorporating vertical linkages and introduce network effects that result in savings in intermediate costs. Our theory posits that the magnitude of these savings may be associated with the effectiveness of knowledge transmission among network participants. Consequently, firms operating in regions with efficient knowledge transmission networks may realize greater savings in intermediate input costs, leading to increased profits from local and export sales. In a last step, we provide empirical evidence supporting our theoretical predictions by demonstrating the positive impact of buyer networks based on relationship-specific products on domestic firm revenues.
Keywords: F12; F15; R12; 330; new trade theory; vertical linkages; network effects.